2019
DOI: 10.1186/s13104-019-4148-9
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia and associated factors among women using hormonal contraceptives in Harar town, Eastern Ethiopia

Abstract: Objective Dyslipidemia is abnormal amount of lipid in blood. Hormonal contraceptives affect lipid metabolism and can enhance the risk of vascular disease like atherosclerosis. In Harar, among contraceptive users, biochemical changes follow up is almost none and magnitude of dyslipidemia is not known. Therefore this study is designed to determine prevalence of dyslipidemia and its predisposing factors. Accordingly, cross-sectional study was conducted from April to June 2014 among hormonal contracep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
27
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 11 publications
10
27
4
Order By: Relevance
“…The present finding is consistent with the results reported in Palestine (66.4%) [18] and South Africa (67.3%) [19]. However, the prevalence of dyslipidemia in this study is higher than the previous findings reported in Eastern Ethiopia (34.8%) [11], Africa PLOS ONE (25.5%) [9], China (32.2%) [20], Iran (30.0%) [21], India (50.7%) [22], and Uganda (63.3%) [23]. Contrary to this, the prevalence is lower than previous studies reported in Lithuania (89.7%) [24], South Africa (85.0%) [25], India (78.4%) [26] and Poland (77.2%) [27].…”
Section: Plos Onesupporting
confidence: 92%
See 2 more Smart Citations
“…The present finding is consistent with the results reported in Palestine (66.4%) [18] and South Africa (67.3%) [19]. However, the prevalence of dyslipidemia in this study is higher than the previous findings reported in Eastern Ethiopia (34.8%) [11], Africa PLOS ONE (25.5%) [9], China (32.2%) [20], Iran (30.0%) [21], India (50.7%) [22], and Uganda (63.3%) [23]. Contrary to this, the prevalence is lower than previous studies reported in Lithuania (89.7%) [24], South Africa (85.0%) [25], India (78.4%) [26] and Poland (77.2%) [27].…”
Section: Plos Onesupporting
confidence: 92%
“…Besides, the overall prevalence of elevated total cholesterol, high LDL-C, low HDL-C, and elevated triglyceride was 25.5%, 21.4%, 19.5%, and 17.0%, respectively [9]. Advanced age, raised FBG, drinking coffee, and vegetable intake were identified as significant predictors of dyslipidemia among women contraceptive users in Eastern Ethiopia [11].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…These results second to several similar studies. Research conducted in Harar found that acceptors of DMPA injection had higher total cholesterol levels than other contraceptives in the amount of 189.35 mg/dL ± 20 mg/dL (Sufa et al, 2019). According to the research conducted in Pakistan on the comparison between DMPA injection acceptors and the control group showed the results of DMPA total cholesterol levels of 180.7 ± 38.8 mg/dL and the controls of 133.03 ± 14.8 mg/dL with the statistical results p = 0.001 which shows that there are very significant differences in cholesterol levels in each group (Dilshad et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…It is also influenced by the length of use of contraception. In the users with a duration of >42 months, there are 75% of users identified as dyslipidemia (Sufa et al, 2019).…”
Section: Discussionmentioning
confidence: 99%